A didactical design research on think-talk-write integrated with GeoGebra: Promoting mathematical communication and collaborative learning - Vivi Rindastri; Endang Wahyuningrum; Sudirman Sudirman; Riyan Hidayat (Nashir Al-Kutub Indonesia, 2026)
This study investigated the effectiveness of a Think-Talk-Write (TTW) strategy integrated with GeoGebra in promoting mathematical communication ability and collaborative learning among Grade X secondary school students. Employing a quasi-experimental design with a non-equivalent control group, the study involved 34 students in the experimental group (TTW-GeoGebra) and 32 students in the control group (conventional instruction) at SMA Negeri 3 Tanjung Raja during the 2025/2026 academic year. Data were collected using a 10-item mathematical communication test and a 15-item collaboration questionnaire, both of which demonstrated good reliability (α = 0.883 and α = 0.866, respectively). Results indicated that the TTW-GeoGebra model produced a moderate improvement in mathematical communication (n-gain = 0.59) and a high improvement in collaborative learning (n-gain = 0.75) in the experimental group, both significantly exceeding the control group’s gains (p < 0.001). Between-group comparisons confirmed that the TTW-GeoGebra model was significantly more effective than conventional instruction for both outcomes. These findings suggest that embedding GeoGebra as a didactic medium across all TTW phases constitutes a principled instructional design for simultaneously developing mathematical communication and collaboration, consistent with NCTM’s process standards and Indonesia’s Kurikulum Merdeka.